Two Novel Yersinia pestis Bacteriophages with a Broad Host Range: Potential as Biocontrol Agents in Plague Natural Foci - Haixiao Jin; Youhong Zhong; Yiting Wang; Chuanyu Zhang; Jin Guo; Xiaona Shen; Cunxiang Li; Ying Huang; Haoming Xiong; Peng Wang; Wei Li (Viruses, 2022)
Bacteriophages (phages) have been successfully used as disinfectors to kill bacteria in food and the environment and have been used medically for curing human diseases. The objective of this research was to elucidate the morphological and genomic characteristics of two novel Yersinia pestis phages, vB_YpeM_ MHS112 (MHS112) and vB_YpeM_GMS130 (GMS130), belonging to the genus Gaprivervirus, subfamily Tevenvirinae, family Myoviridae. Genome sequencing showed that the sizes of MHS112 and GMS130 were 170507 and 168552 bp, respectively. A total of 303 and 292 open reading frames with 2 tRNA and 3 tRNA were predicted in MHS112 and GMS130, respectively. The phylogenetic relationships were analysed among the two novel Y. pestis phages, phages in the genus Gaprivervirus, and several T4-like phages infecting the Yersinia genus. The bacteriophage MHS112 and GMS130 exhibited a wider lytic host spectrum and exhibited comparative temperature and pH stability. Such features signify that these phages do not need to rely on Y. pestis as their host bacteria in the ecological environment, while they could be based on more massive Enterobacteriales species to propagate and form ecological barriers against Y. pestis pathogens colonised in plague foci. Such characteristics indicated that the two phages have potential as biocontrol agents for eliminating the endemics of animal plague in natural plague foci.